2011
DOI: 10.1002/pssa.201127034
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature DC magnetron sputtering deposition and field emission of Al‐doped ZnO films

Abstract: Al doped ZnO films were prepared by reactive direct current (DC) magnetron sputtering at room temperature. The targets were metallic Al and Zn while the gases were Ar and O2. X‐ray diffraction (XRD) shows that the films are of hexagonal structure and Al is successfully doped into ZnO without secondary phases detected. Raman scattering spectra of the films contain the E1 mode of ZnO. Seebeck effect shows that the films are n‐type and four probe instrument shows that the films are very resistive. The high resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…15 F. Ye et al reported eld emission of Al-doped ZnO lms by using DC magnetron sputtering. 16 K. Mahmood et al reported the enhanced and stable eld emission behavior of a novel electrosprayed Al-doped ZnO bilayer lm by using electrosprayed method (>160 C). 17 C. L. Hsu et al reported enhanced eld emission of Al-doped ZnO nanowires grown on a exible polyimide substrate by using hydrothermal method (>90 C).…”
Section: Introducionmentioning
confidence: 99%
“…15 F. Ye et al reported eld emission of Al-doped ZnO lms by using DC magnetron sputtering. 16 K. Mahmood et al reported the enhanced and stable eld emission behavior of a novel electrosprayed Al-doped ZnO bilayer lm by using electrosprayed method (>160 C). 17 C. L. Hsu et al reported enhanced eld emission of Al-doped ZnO nanowires grown on a exible polyimide substrate by using hydrothermal method (>90 C).…”
Section: Introducionmentioning
confidence: 99%